2009
DOI: 10.3767/003158509x415450
|View full text |Cite
|
Sign up to set email alerts
|

<I>Phytophthora multivora</I> sp. nov., a new species recovered from declining <I>Eucalyptus</I>, <I>Banksia</I>, <I>Agonis</I> and other plant species in Western Australia

Abstract: A new Phytophthora species, isolated from rhizosphere soil of declining or dead trees of Eucalyptus gomphocephala, E. marginata, Agonis flexuosa, and another 13 plant species, and from fine roots of E. marginata and collar lesions of Banksia attenuata in Western Australia, is described as Phytophthora multivora sp. nov. It is homothallic and produces semipapillate sporangia, smooth-walled oogonia containing thick-walled oospores, and paragynous antheridia. Although morphologically similar to P. citricola, phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
156
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(161 citation statements)
references
References 51 publications
5
156
0
Order By: Relevance
“…2b). Morphology and size were consistent with the range reported for P. multivora (Scott et al 2009). Koch's postulates were not undertaken due to the diversity and maturity of the hosts.…”
supporting
confidence: 77%
“…2b). Morphology and size were consistent with the range reported for P. multivora (Scott et al 2009). Koch's postulates were not undertaken due to the diversity and maturity of the hosts.…”
supporting
confidence: 77%
“…Phytophthora multivora has been isolated from declining E. gomphocephala in the same region as this study (Scott et al 2009), and demonstrated to cause loss of fine roots in E. gomphocephala seedlings in containers (Scott et al 2011). Recently, fewer ECM fungal mats have been observed in declining E. gomphocephala stands (Scott et al 2012).…”
Section: Discussionsupporting
confidence: 50%
“…One of these is Eucalyptus gomphocephala (tuart), a woodland tree endemic to the Swan Coastal Plain of Western Australia (Elridge et al 1994), that has experienced a marked reduction in health and vitality (known as tuart decline) (Archibald et al 2010;Cai et al 2010) locally reaching up to 90 % mortality across all age classes (Tuart Response Group 2002). The cause is unknown, and several physical and biological factors might be involved (Close et al 2009;Archibald et al 2010) including soil bacteria and fungi (Scott et al 2009;Cai et al 2010;Scott et al 2011). In particular, mycorrhizal fungi may be important in the health of E. gomphocephala.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, P. inundata has also been associated with dying horticultural shrubs and trees including Aesculus, Olea, Salix, Prunus and Vitis (Brasier et al 2003b;Cunnington et al 2006). P. multivora and P. cryptogea were rarely encountered in waterways in this study, but both species are commonly associated with numerous dead and dying native hosts Scott et al 2009). This is the first report of P. multivora in water in Australia, but it has been recorded in New Zealand waterways (Randall 2011).…”
Section: Discussionmentioning
confidence: 99%